The genus Mytilina in China, with description of a new species (Rotifera: Monogononta: Mytilinidae) - Luo, Yongting; Segers, Hendrik (Zootaxa, 2014)
During our study of biodiversity of Rotifera in PR China, as model taxon of freshwater Micrometazoa, we came across several records that warrant revision regarding species of genus Mytilina Bory de St. Vincent, 1826 (Rotifera, Monogonta, Mytilinidae). In addition to this review we describe a new species encountered during examination of freshwater habitats of Inner Mongolia, P.R.China. This new species, Mytilina wangi n. sp., appears to belong to the Mytilina mucronata - ventralis complex but differs from the known taxa in the group by its domed lorica and relatively short toes. We provide an annotated checklist of the Chinese representatives of the genus and discuss the species of the M. mucronata-ventralis group. We suggest treating M. brevispina (Ehrenberg, 1830) and M. ventralis (Ehrenberg, 1830)(synonym: M. macracantha (Gosse, 1886)) as separate species-level taxa rather than as two infrasubspecific variants of the same species, and argue that Mytilina trigona var. bispinosa Wang, 1961 is a misidentified M. acanthophora Hauer, 1938 rather than an infrasubspecific variant of M. trigona (Gosse, 1851).